Knowledge Gaps in Biophysical Changes After Powered Robotic Exoskeleton Walking by Individuals With Spinal Cord Injury—A Scoping Review - Yip, Christopher C. H.; Lam, Chor-Yin; Cheung, Kenneth M. C.; Wong, Yat Wa; Koljonen, Paul A. (Frontiers in Neurology, 2022)
In addition to helping individuals with spinal cord injury (SCI) regain the ability to ambulate, the rapidly evolving capabilities of robotic exoskeletons also provide an array of secondary biophysical benefits which can reduce the complications resulting from prolonged immobilization. Proposed benefits of increased life-long over-ground walking capacity include improved upper body muscular fitness, improved circulatory response, improved bowel movement regularity, and reduced pain and spasticity. Beyond the positive changes related to physical and biological function, exoskeletons have also been suggested to improve SCI individuals’ quality of life (QOL) by allowing increased participation in day-to-day activities. Most of the currently available studies which have reported on the impact of exoskeletons on the QOL and prevention of secondary health complications on individuals with SCI, are of small scale and are heterogenous in nature. Moreover, few meta-analyses and reviews have attempted to consolidate the dispersed data to reach more definitive conclusions of the effects of exoskeleton use. This scoping review seeks to provide an overview on the known effects of overground exoskeleton use, on the prevention of secondary health complications, changes to the QOL, as well as their effect on independence of SCI individuals in the community settings. The intent of the review is also to identify gaps in the literature currently available, and to make recommendations on focus study areas and methods for future investigations.